Renewal of Director’s Criminal Liability for BUMN Losses Based on Business Judgment Rule - Triantono; Marizal, Muhammad (Fakultas Hukum Universitas Widya Mataram, 2024)
One of the problematic issues in existence of BUMN is the uncertainty in determining whether BUMN is a representation of the state or fully a business entity. This is due to the absence of an understanding of the BUMN's capital originating from separated state assets. This condition in turn has an impact on the uncertainty of the criminal responsibility of the directors if the BUMN suffers a loss associated with The Principle of State Losses and The Principle of Business Judgment Rule as one of the universal principles in company management. Based on this, there are two problems, namely: 1) What is the importance of The Business Judgment Rule Principle in the management of BUMN’s in Indonesia? 2) How is the criminal responsibility of the Board of Directors for the loss of BUMN related to the Business Judgment Rule Principle? This study is a normative juridical study conducted through a literature study using legal materials to produce an analytical description in order to answer the problems posed. The results of this study show that The Principle of Business Judgment Rule has an important position in ensuring the protection of directors who run the company based on Good Faith and Condor. The renewal of the board of directors' criminal liability for BUMN losses based on the Business Judgment Rule Principle has the direction (Ius Constituendum) of revising the BUMN Law in the form of reconceptualization and strengthening of The Principles of Good Faith and Good Will through the framework of good corporate governance.